Sustainability-Based Mangrove Ecotourism Management Strategy Using ADO-ODTWA and MDS Approaches: A Case Study of Ngusulenge Mangrove Area, Maitara Island, Indonesia - Salim Abubakar; Rina; Irmalita Tahir; Rene C. Kepel; Yusri Sapsuha; Andy Kurniawan; Riyadi Subur; Faizal Rumagia (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research The mangrove ecosystem on a small island is the object of this research. The Ngusulenge mangrove area in Maitara Tengah Village is worthy of development as a sustainable ecotourism destination with a medium to high attractiveness value based on ecological and accessibility aspects. Dimensionally, the social dimension has the highest sustainability value compared to the other dimensions. However, all dimensions require more serious improvement efforts to meet the needs of developing a mangrove ecotourism area on Maitara Island. Collaboration between stakeholders, supported by clear regulations regarding the management of mangrove ecotourism areas, will accelerate regional development and improve the welfare of communities involved in the management and utilization of coastal ecosystems and small islands. Abstract Sustainable mangrove ecotourism requires a balanced focus across ecological, economic, and social dimensions to ensure long-term conservation and community benefits. In line with the concept of sustainability, the development of mangrove ecotourism must prioritize tourist attractions, local community involvement, and environmental conservation. This study assessed tourism feasibility and multidimensional sustainability of Ngusulenge mangrove ecotourism using ADO-ODTWA and Rap-Mforest using interdisciplinary approach for sustainable mangrove ecotourism management. This study employs an interdisciplinary approach to sustainable ecotourism management, utilizing ADO-ODTWA analysis to assess tourist attractions and the feasibility of ecotourism development, and to identify potential tourist attraction resources. Additionally, it employs Rap-Mforest analysis to measure the sustainability status of ecotourism in ecological, social, economic, and institutional aspects. The results of the study indicate that the Ngusulenge mangrove area in Maitara Tengah Village shows potential as a sustainable ecotourism destination with medium to high attraction values based on ecological and accessibility aspects with an ADO-ODTWA index value (82.44%) indicating suitability for development, while the multidimensional sustainability index value (41.60%) falls into the less sustainable category, but requires major interventions in several factors, such as cleanliness, accommodation, and socio-economic management, to overcome the challenges of mangrove ecosystem degradation. The lowest feasibility factor value was found in the Accommodation criterion (58.33%), and the lowest value for the sustainability dimension was found in the Institutional dimension (37.07%). The collaboration between the government, the community, and regulations needs to be strengthening, enabling the potential of the Ngusulenge mangrove area to become a tourism-based conservation model that potentially supports coastal biodiversity, local empowerment, and inclusive economic growth in North Maluku Province. Institutional weakness indicates the need to strengthen government–community coordination and local regulations.